Determination of Reliability Design of Mechanical Systems - Woo, Seong-Woo; L. O’Neal, Dennis; Mohammed Hassen, Yimer (Novel Perspectives of Engineering Research Vol. 10, 2022)
To enhance the design of mechanical systems, parametric Accelerated Life Testing (ALT) as a systematic reliability method is proposed as a way to identify design imperfections and rectify them in creating a reliable quantitative (RQ) specification. It requires: (1) a parametric ALT scheme shaped on system BX lifetime, (2) a load inspection, (3) parametric ALTs with the associated design modifications, and (4) an assessment of whether the revised product design(s) reach the targeted BX life-time. A general life-stress model and sample size equation are proposed. The redesign of a hinge kit system (HKS) in a refrigerator was a test case employing both market data and parametric ALT. A force and moment balance analysis was used to conduct parametric ALTs. For a refrigerator door, the mechanical impact loadings of the HKS were assessed. The HKS failure occurred in the first ALT due to a crack/fracture in the kit housing, and oil flowed from the damper when the HKS was dismantled. The failure modes and processes developed in the first ALT were comparable to those discovered in failed samples from the marketplace. Stress raisers, such as corner roundings and the rib of the housing in HKS, the seal in the oil damper, and the material of the cover housing were among the HKS design characteristics that were missing. The cover housing fractured in the second ALT. The plastic substance used in the HKS cover housing was a design flaw. The cover housing was changed from plastic to aluminium as part of a corrective action plan. The updated HKS was assured to have a B1 life of 10 years after the second ALT, with a yearly failure rate of 0.1 percent.